Attitude of doctors working in a tertiary hospital towards Do-not-resuscitate decisions - Adhikari, Sunil; Rijal, Suraj (Journal of General Practice and Emergency Medicine of Nepal, 2019)
Introduction: There has been many discussions around the world regarding various forms of end-of-life decisions and healthcare professionals might have different views towards do not resuscitate (DNR) which might have been influenced by the medical education, especially after clinical training. Hence this study is designed to explore the attitudes of doctors towards DNR decision.Methodology: This was a descriptive cross-sectional study conducted between August 2016 to November 2016 in Patan Hospital. Preformed structured questionnaires were given and the experience of events occurring around DNR decisions and problems associated with it were assessed. The attitude towards DNR was assessed using Likert scale and calculating their mean scores.Result: Out of 106 respondents, there were total 53 interns and 53 medical officers. Almost all the doctors (96.2%) had experience in CPR and majority (88.7 %) had experience of dealing with death of a patient and had administered CPR even when there was DNR decision. The mean score of the doctor’s attitude towards DNR was 3.44, most of the doctors, especially interns had conflicts with family members while taking DNR decisions.Conclusion: This study reflects that doctors working in Patan Hospital have a positive attitude towards DNR decisions.